The Challenge of Arabization in Syria (American Journal of Islam and Society, 1994)
The eclipse of Arabic that took place in the last part of the eighteenthand the early nineteenth century was caused by several factots. This paperlooks at the mxons for this eclipse and also sheds light on the revival ofArabic in the Arab world in general and in Syria in particular.The conquest of Syria and Egypt by Salim I in 1516 and 1517 marksa definite stage in the extension of Ottoman sway over the Arab world.His crushing victories made him the master of Iraq and Syria and enabledhim to enter Cairo and establish his rule over Egypt. Under his successor,Sulaymh the Magnificent, the subjection of the Arab world was extendedwestward along the North African coast and southward as far as Yemenand Aden. Upon Stdaymiin’s death in 1566, the Ottomans ruled the Arabworld from Algeria to the Arabian Gulf, and from Aleppo to the IndianOcean. In addition to the sacred cities of Makkah, Madinah, and Jerusalem,it embraced Damascus, the fitst capital of the Arab empire, andBaghdad, whose sciences had once illuminated the world. With varyingfortunes, and frequently accompanied by war and revolt, the OttomanEmpire maintained itself in these territories until the end of the eighteenthcentury and the outbreak of the First World War in 1914.At the beginning of the eighteenth century, the Ottoman Empire witnesseda movement of reform and reorganization under Abmad III(1703-30) and his successors. However, the Arab world did not seem to benefitvery much from it. In addition, these reforms, intended primarily to arrestthe Empire’s decline and restore vitality to its system, sought to establishTurldsh as the language of instruction. Later on, Arabic was abandonedand Turkish became the language of instruction in government schoolsand educational institutions.‘ Only Arabic grammatical rules, which wereindispensable for an understanding of Ottoman literature, were taught and,quite often, by Turkish teachers ...